Frequency of eating alone is associated with adolescent dietary intake, perceived food-related parenting practices and weight status: cross-sectional Family Life, Activity, Sun, Health, and Eating (FLASHE) Study results. Issue 9 (28th February 2019) - Reicks, Marla; Davey, Cynthia; Anderson, Alex Kojo; Banna, Jinan; Cluskey, Mary; Gunther, Carolyn; Jones, Blake; Richards, Rickelle; Topham, Glade; Wong, Siew Sun
Abstract: Objective: To examine relationships between frequency of adolescents eating alone (dependent variable) and diet, weight status and perceived food-related parenting practices (independent variables). Design: Analyses of publicly available, cross-sectional, web-based survey data from adolescents. Setting: Online consumer opinion panel. Subjects: A US nationwide sample of adolescents (12–17 years) completed Family Life, Activity, Sun, Health, and Eating (FLASHE) Study surveys to report demographic and family meal characteristics, weight, dietary intake, home food availability and perceptions of parenting practices. Parents provided information about demographic characteristics. Logistic regression analyses were used to test for associations between variables. Results: About 20 % of adolescents reported often eating alone ( n 343) v . not often eating alone ( n 1309). Adjusted odds of adolescents often eating alone were significantly higher for non-Hispanic Black compared with non-Hispanic White adolescents (OR=1·7) and for overweight or obese compared with normal- or underweight adolescents (OR=1·6). Adjusted odds of adolescents eating alone were significantly lower for those who reported that fruits and vegetables were often/always available in the home (OR=0·65), for those who perceived that parents had expectations about fruit and vegetable intake (OR=0·71) and for those who agreed with parental authority to make rules about intake of junk food/sugary drinks (OR=0·71). Junk food and sugary drink daily intake frequency was positively associated with often eating alone. Conclusions: Often eating alone was related to being overweight/obese, having less healthy dietary intake and perceptions of less supportive food-related parenting practices.